The global downturn and its impact on euro area exports and competitiveness - Filippo di Mauro; Katrin Forster; Ana Lima (European Central Bank (ECB), 2010)
World trade contracted sharply in late 2008 and early 2009 following the deepening of the financial crisis in September 2008. This paper discusses the main mechanisms behind the global downturn in trade and its impact on euro area exports and competitiveness. It finds that the euro area was hit particularly hard by the contraction in global demand. Moreover, the collapse in the demand for euro area products during the downturn was exacerbated to some degree by unfavourable developments in price competitiveness, resulting in further losses in competitiveness compared to our main trading partners, in line with pre-crisis trends. This view is also confi rmed by evidence from broad-based competitiveness measures, which show that euro area countries recorded losses in productivity during this period. Going forward, the recovery in world trade will depend mainly on a resurgence in global demand and its expenditure composition. With regard to the euro area, as the global economy recovers at varying speeds and given the current growth momentum in emerging economies, the performance of the external sector may be hindered by the geographical orientation of its export markets, which are mainly focused on advanced economies and other EU member states. Furthermore, the strength and sustainability of the recovery in exports will also depend on the structuring process undertaken by European fi rms in response to globalisation-related challenges. Governments within the European Union should therefore focus on policies to strengthen competition and increase market integration, in order to benefit fully from the globalisation process going forward. In contrast, a resurgence in global protectionist policies could dampen the prospects for world and euro area trade and should be strongly resisted.
Keywords: C32; O11; 330; competitiveness; euro area; Trade; Export; Außenhandelsstruktur; Internationaler Wettbewerb; Internationale Wirtschaftsbeziehungen; Finanzkrise; Eurozone; EU-Staaten